2021
DOI: 10.48550/arxiv.2107.07569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of optically thin cooling curves on condensation formation: Case study using thermal instability

Joris Hermans,
Rony Keppens

Abstract: Context. Non-gravitationally induced condensations are observed in many astrophysical environments. In solar physics, common phenomena are coronal rain and prominences. These structures are formed due to energy loss by optically thin radiative emission. Instead of solving the full radiative transfer equations, precomputed cooling curves are typically used in numerical simulations. In the literature, a wide variety of cooling curves exist, and they are quite often used as unquestionable ingredients. Aims. We he… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Many other optically thin cooling curves, such as from Schure et al (2009), are also available in MPI-AMRVAC. Hermans & Keppens (2021) showed that changing the cooling curve does not truly change whether condensations happen, but only impacts the growthrate of the thermal instability and the morphology of the formed condensations.…”
Section: Methodsmentioning
confidence: 99%
“…Many other optically thin cooling curves, such as from Schure et al (2009), are also available in MPI-AMRVAC. Hermans & Keppens (2021) showed that changing the cooling curve does not truly change whether condensations happen, but only impacts the growthrate of the thermal instability and the morphology of the formed condensations.…”
Section: Methodsmentioning
confidence: 99%
“…Λ(T ) is set to be zero below 10,000 K because the plasma there is no longer fully ionized and becomes optically thick. Many optically thin cooling curves have been implemented in MPI-AMRVAC, and Hermans & Keppens (2021) studied the influence of these cooling curves on condensation formation and found that for different cooling curves, condensations may have different formation times and morphology. H is the heating term which includes the background heating and localized heating H = H bgr + H loc .…”
Section: Governing Equationsmentioning
confidence: 99%